Transcatheter closure of patent ductus arteriosus in preterm infants: results from a single-center cohort - Honnorat, Marion; Perouse-De-Montclos, Thomas; Bakloul, Mohamed; Walton, Camille; Butin, Marine; Vo Van, Philippe (Frontiers in Pediatrics, 2023)
To assess the success rate of patent ductus arteriosus (PDA) transcatheter closure in preterm infants and to describe the nature of procedural adverse events and short-term clinical status.All the preterm infants with PDA transcatheter closure were evaluated retrospectively between July 2019 and March 2023 in a single level III neonatal intensive care unit in France. The procedure was performed in the catheterization laboratory using venous canulation. We retrospectively collected data about the patients' characteristics, procedural outcomes and complications.Twenty-five infants born between 23.4 and 32.0 weeks of gestational age (mean ± SD 26.3 ± 1.9 weeks) underwent transcatheter PDA closure. Their mean age and weight at the time of the procedure were 52 days (range 22-146 days) and 1620 g (range 890-3700 g), respectively. Successful closure was achieved in all but one patient. Procedure related complications were reported in 10 infants (40%), including 6 left pulmonary artery stenosis one of which required a balloon dilatation, two cardiac tamponades and two inferior vena cava thrombosis. Only two post-ligature syndromes occurred after the procedure. Two infants died one of which was related to the procedure.Transcatheter closure of a PDA is a valid alternative to surgical ligation due to its high success rate and low incidence of post-ligature syndrome. Nevertheless, we also report rare, although serious complications.